Usefulness of intracardiac echocardiography with a mechanical probe for catheter‐based interventions: A 10‐year prospective registry. Issue 9 (4th June 2014) - Rigatelli, Gianluca; Dell'Avvocata, Fabio; Giordan, Massimo; Viceconte, Nicola; Osanna, Rocco Aldo; Braggion, Gabriele; Aggio, Silvio; Cardaioli, Paolo; Chen, Jack P.
ABSTRACT Background The clinical outcome benefit of intracardiac echocardiography (ICE) with a mechanical probe during congenital heart disease interventions has not been fully investigated. We reported the long‐term results of a prospective registry of interatrial shunt closure guided by mechanical ICE. Methods We enrolled 537 patients (mean age 48 ± 19.0 years, 378 females) submitted to ICE‐aided procedures in a prospective registry over a 10‐year period (September 2003‐September 2013). All patients underwent transesophageal echocardiography (TEE) before the planned procedure. We evaluated (1) structure identification capability, (2) fossa ovale and interatrial septum component measurement, (3) procedure monitoring capability, (4) procedural and fluoroscopy times, and radiograph dose, (5) probe‐related complications. Results ICE was successfully performed and was able to correctly identify the structures previously assessed by TEE in all patients. In 24 patients (4.5%), ICE allowed better anatomy definition than TEE. In 35 other patients (6.5%), ICE identified structures not observed by TEE, which led to change indications to interventions or the operative technique to be used. In 131 patients (24.4%), ICE evaluation led to change the planned device to be implanted. There was only one probe‐related complication (0.2%). Conclusions Mechanical ICE may offer a valid alternative to conventional TEE in guiding congenital heart disease interventional procedures. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:534–543, 2014